Exploring the potential of 5 commercial essential oils to inhibit the proliferation of A549 lung cancer cells - Abdullah, Nazurah; Hazahari, Noor Yuslida; Ahmad Nor, Yusilawati; Amid, Azura; Samsudin, Nurhusna (IIUM Press, 2024)
Globally, lung cancer stands as the primary cause of cancer-related fatalities, securing a spot among the top 10 in newly reported cases. The late detection of lung cancer is often attributed to its indication through commonplace symptoms like coughing. Seeking alternatives, this research investigated the medicinal potential of certain essential oils (EOs) with a rich history in traditional medicine. The study aimed to assess the effectiveness of 5 EOs — Clary Sage, Frankincense, Marjoram, Myrrh, and Thyme as a halal alternative therapy for lung cancer A549 cell line. Notably, based on these investigations’ findings, Myrrh and Thyme emerged as promising candidates, displaying significant capability to inhibit lung cancer cell expansion. Myrrh had the lowest IC50 value, 19 μg/mL, followed by Thyme, 45 μg/mL. In optimisation research, Myrrh resulted in 85% inhibition after 72 hours of exposure to 800 μg/mL concentration. Myrrh demonstrated reduced cell generation and growth rates for cytokinetic study and increased cell death rate. In conclusion, this research was designed to explore the cytotoxic effects of EOs on lung cancer cells using the A549 cell line, leading to the identification of a potential alternative source of halal-compliant pharmaceuticals.